Treatments for dry age-related macular degeneration and Stargardt disease: a systematic review - Norman Waugh; Emma Loveman; Jill Colquitt; Pamela Royle; Jian Lee Yeong; Geraldine Hoad; Noemi Lois (Health Technology Assessment, 2018)
Background: Age-related macular degeneration (AMD) is the leading cause of visual loss in older people. Advanced AMD takes two forms, neovascular (wet) and atrophic (dry). Stargardt disease (STGD) is the commonest form of inherited macular dystrophy. Objective: To carry out a systematic review of treatments for dry AMD and STGD, and to identify emerging treatments where future NIHR research might be commissioned. Design: Systematic review. Methods: We searched MEDLINE, EMBASE, Web of Science and The Cochrane Library from 2005 to 13 July 2017 for reviews, journal articles and meeting abstracts. We looked for studies of interventions that aim to preserve or restore vision in people with dry AMD or STGD. The most important outcomes are those that matter to patients: visual acuity (VA), contrast sensitivity, reading speed, ability to drive, adverse effects of treatment, quality of life, progression of disease and patient preference. However, visual loss is a late event and intermediate predictors of future decline were accepted if there was good evidence that they are strong predictors of subsequent visual outcomes. These include changes detectable by investigation, but not necessarily noticed by people with AMD or STGD. ClinicalTrials.gov, the World Health Organization search portal and the UK Clinical Trials gateway were searched for ongoing and recently completed clinical trials. Results: The titles and abstracts of 7948 articles were screened for inclusion. The full text of 398 articles were obtained for further screening and checking of references and 112 articles were included in the final report. Overall, there were disappointingly few good-quality studies (including of sufficient size and duration) reporting useful outcomes, particularly in STGD. However we did identify a number of promising research topics, including drug treatments, stem cells, new forms of laser treatment, and implantable intraocular lens telescopes. In many cases, research is already under way, funded by industry or governments. Limitations: In AMD, the main limitation came from the poor quality of much of the evidence. Many studies used VA as their main outcome despite not having sufficient duration to observe changes. The evidence on treatments for STGD is sparse. Most studies tested interventions with no comparison group, were far too short term, and the quality of some studies was poor. Future work: We think that the topics on which the Health Technology Assessment (HTA) and Efficacy Mechanism and Evaluation (EME) programmes might consider commissioning primary research are in STGD, a HTA trial of fenretinide (ReVision Therapeutics, San Diego, CA, USA), a visual cycle inhibitor, and EME research into the value of lutein and zeaxanthin supplements, using short-term measures of retinal function. In AMD, we suggest trials of fenretinide and of a potent statin. There is epidemiological evidence from the USA that the drug, levodopa, used for treating Parkinson’s disease, may reduce the incidence of AMD. We suggest that similar research should be carried out using the large general practice databases in the UK. Ideally, future research should be at earlier stages in both diseases, before vision is impaired, using sensitive measures of macular function. This may require early detection of AMD by screening. Study registration: This study is registered as PROSPERO CRD42016038708. Funding: The National Institute for Health Research HTA programme.